Low-dose IL-2 therapy limits the reduction in absolute numbers of peripheral lymphocytes in systemic lupus erythematosus patients with infection. (3rd June 2022) - Zhang, Jia-Qian; Zhang, Sheng-Xiao; Wang, Jia; Qiao, Jun; Qiu, Meng-Ting; Wu, Xiao-Yan; Chen, Jun-Wen; Gao, Chong; Li, Xiao-Feng
Abstract: Background: Systemic lupus erythematosus (SLE) is a heterogeneous autoimmune disorder characterized by disturbed cellular and humoral immune responses. Dysregulations of immune system and immunosuppressive medications predispose SLE patients to infection. This study aims to investigate the alterations and absolute concentrations of lymphocyte subpopulations in SLE patients with different infection and their responses of low-dose IL-2 therapy. Methods: A total of 333 patients with SLE without recent infection, 162 patients suffering infection, and age and sex-matched 132 healthy controls (HCs) were recruited. Of them, 54 SLE patients (including 41 non-infected group and 13 infected group) received a 5-day course of low-dose IL-2 administration at a dose of 0.5 million IU per day. Lymphocyte subpopulations were analyzed by flow cytometry. Results: Patients with SLE had lower levels of lymphocyte subpopulations in peripheral blood such as T, B, NK, CD4 + T, CD8+ T, Th1, Th2, Th17, and Treg cells, and the reduction in these cells was more obvious in patients with infection ( p  <.05 to p < .01). Low-dose IL-2 effectively expanded T ( p  <.001), B ( p  <.001), CD4 + T ( p  <.01), CD8 + T ( p  <.001), Th1 ( p  <.01), Th17 ( p  <.1), and Treg cells ( p  <.01) of SLE patients, these cells were comparable to that of HCs after the IL-2 treatment. Conclusions: Patients with SLE had insufficiency of circulating lymphocyte subsets. This phenomenon was more obverse in those accompanying infection, suggesting the low concentration of lymphocytes may be used as indicators of high infection risk in SLE patients. Low-dose IL-2 induced expansion of Treg cells and NK cells, which may contribute to the restoration of immune homeostasis in SLE patients.